El TDHA a través de los ojos de una maestra - Camargo Zamata, Marisol (2016)
The ADHD is a disorder which affects nearly twelve percent of students. The characteristics are predominantly impulsive, deconcentration, restlessness and constant body movement. The assistance of several professionals is required to handle, including doctors, psychologists and teachers. Teachers should be well informed so that in the classroom we can better control the situations of children and lead them in a professional way and with enormous teaching resources that will support the successful management of this problem.